Remdesivir and hospitalization outcomes in patients with COVID -19 in the period of SARS-CoV-2 Delta circulation - D. V. Litvinchuk; D. E. Danilov; I. A. Karpov (Журнал инфектологии, 2025)
Aim of the study is to analyze the effect of remdesivir on the outcome of hospitalization in patients with COVID-19 during the period of the SARS-CoV-2 Delta predominance. Material and methods. Among 11203 patients hospitalized from the pandemics start until June 2023 in the Minsk City Clinical Hospital for Infectious Diseases (Republic of Belarus), 3085 patients admitted during SARS-CoV-2 Delta variant predominance (June 2021 – January 2022). After applying exclusion criteria, the final cohort included 2940 patients, of whom 27,7% (813/2940) received remdesivir. Survival analysis was performed using Cox proportional hazards model, stratified by respiratory failure status at admission. The model included remdesivir and dexamethasone administration, symptom duration, comorbidities, sex, and age as covariates. P-values < 0,05 were considered to be statistically significant. Statistical analysis was performed in R v.4.4.1 with libraries: dplyr, tidyr, survival, survminer, matchit, gtsummary, forplo.Results. The 28-day survival among patients with remdesivir use and respiratory failure at baseline was 86,5 (79,9-93,6)%, and 91,3 (85,6-97,4)% in patients without respiratory failure. In patients without remdesivir use, the 28-day survival in those with respiratory failure at baseline was 77,9 (69,4-87,5)%, and 85,6 (77,3-94,8)% in patients without respiratory failure. In the Cox proportional hazards model stratified by baseline respiratory failure status, remdesivir use was associated with significantly lower mortality (adjusted HR 0,58, 95% CI 0,39-0,88; p=0,01) after adjustment for sex, age, comorbidities, and dexamethasone administration.Conclusion. Remdesivir was effective in decreasing inhospital mortality during the predominance of the SARSCoV-2 Delta variant.